Characteristics of Concentrated Yogurt Manufactured from Goat Milk Added with Different Levels of Black Rice Extract - Sulistyorini, Dewi Wulandari; Fadhlurrohman, Irfan; Tianling, Mays; Setyawardani, Triana; Sumarmono, Juni (Jurnal Agripet, 2025)
This study investigated the characteristics of concentrated yogurt made from goat milk with the addition of black rice extract. The inclusion of black rice extract aimed to provide a source of antioxidants and natural coloring, as it is rich in flavonoids, particularly anthocyanins. The primary materials used in this research were goat milk, a dry yogurt starter, and black rice extract. The experiment was conducted in several stages: preparation of black rice extract, yogurt production, and concentrated yogurt production. A randomized complete block design (RCBD) was employed, with treatments involving varying levels of black rice extract (0%, 2%, 4%, and 6%), each treatment repeated five times. The yogurt starter, containing probiotic lactic acid bacteria (Bifidobacterium longum, Lactobacillus rhamnosus, Lactobacillus casei, Lactobacillus helveticus, Lactobacillus bulgaricus, Lactobacillus acidophilus, and Streptococcus thermophilus), was used to facilitate the fermentation of milk into yogurt. Parameters measured included yield, pH, total titratable acidity, instrumental color indices (L*, a*, b*, whiteness index, hue, and chroma), total phenolic compounds, antioxidant activity, total lactic acid bacteria (LAB), texture, and proximate composition (moisture, ash, fat, and protein content). The addition of black rice extracts up to 6% resulted in higher protein and total lactic acid bacteria levels compared to the control. Additionally, black rice extract improved the color characteristics of concentrated yogurt made from goat milk.and gastrointestinal tract development in broiler chickens.